2012
DOI: 10.1016/j.jus.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral stress fracture of the tibia diagnosed by ultrasound. A case report

Abstract: KEYWORDSFatigue fracture; Sonography; Ultrasound; Stress fracture.Abstract We report the case of a 35 years old patient presenting with bilateral pain in the medial aspect of both knees. Ultrasound examination revealed hyperechoic appearance of the subcutaneous tissue and periarticular soft tissue bilateral. Color Doppler studies showed significant vascular signals at the surface of the tibial plateaux. US appearance, together with clinical findings, suggested a diagnosis of simultaneous bilateral fatigue frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…An MRI confirmed the diagnosis and the patient's symptoms resolved with rest. They reported USG may be a useful imaging tool in the diagnosis of stress fracture 13 . In our case we did not performed USG to our patient.…”
Section: Discussionmentioning
confidence: 68%
“…An MRI confirmed the diagnosis and the patient's symptoms resolved with rest. They reported USG may be a useful imaging tool in the diagnosis of stress fracture 13 . In our case we did not performed USG to our patient.…”
Section: Discussionmentioning
confidence: 68%
“…The potential diagnostic accuracy of using US for bone stress injury detection has remained a topic of scientific interest . In 2008, a double‐blind study by Farkash compared the diagnostic accuracy of US with a linear transducer (range, 5.5–12.0 MHz) to bone scintigraphy using 25‐mCi technetium Tc 99m methylene diphosphonate.…”
Section: Historical Review Of Imaging Modalities Used In the Diagnosimentioning
confidence: 99%
“…Similar to MRI, US shows the early phase soft tissue findings of bone stress injuries (grade 1 injury revealed by MRI), as well as cortical fracture (grade 4 injury revealed by MRI). Cortical fracture may be seen on US, as evidenced by a cortical disruption or breakage, especially in long bones, a small fluid collection, soft tissue edema, or local vessel disruption …”
Section: Anatomic Findings On Imagingmentioning
confidence: 99%
“…The normal periosteum, depending on its thickness, can sometime difficult to assess by sonography. Due to its tomographic capabilities, sonography can show acute fractures that are difficult to image on radiography and can show a variety of stress fractures . A recent study on sonographic and radiographic capabilities in the early detection of metatarsal stress fractures showed that sonography had sensitivity of 83% and specificity of 76% (correlated with MRI) and that sonography was more sensitive than standard radiography for this purpose …”
Section: Discussionmentioning
confidence: 99%